Redox Regulation of Heart Regeneration: An Evolutionary Tradeoff - Elhelaly, Waleed M.; Lam, Nicholas T.; Hamza, Mohamed; Xia, Shuda; Sadek, Hesham A. (Frontiers in Cell and Developmental Biology, 2016)
Heart failure is a costly and deadly disease, affecting over 23 million patients worldwide, half of which die within 5 years of diagnosis. The pathophysiological basis of heart failure is the inability of the adult heart to regenerate lost or damaged myocardium. Although limited myocyte turnover does occur in the adult heart, it is insufficient for restoration of contractile function[1-6]. In contrast to lower vertebrates which can regenerate their myocardium through cardiomyocyte proliferation,[7-13], adult mammalian heart cardiomyogenesis very limited[1-5]. Studies in the late 90s elegantly demonstrated that mammalian cardiomyocytes continue to divide for a few days after birth [14-16], only to undergo permanent cell cycle arrest shortly thereafter. Recently, we demonstrated that resection of up to 15% of the apex of the left ventricle of postnatal day 1 (P1) mice results in complete regeneration within 21 days following injury, without significant fibrosis and cardiac dysfunction[17]. Moreover, we described a similar regenerative response following ischemic myocardial infarction [18]. This response was well characterized by robust cardiomyocyte proliferation, with gradual restoration of normal cardiac morphology and function. In addition to the histological evidence of proliferating myocytes, genetic fate-mapping studies confirmed that the majority of newly formed cardiomyocytes are derived from proliferation of preexisting cardiomyocytes[17]. Intriguingly, this regenerative capacity is lost by P7, after which injury results in the cardiomyocyte hypertrophy and scar-formation, which coincides with binucleation and cell cycle exit of cardiomyocytes [14, 19]. An important approach to understanding the loss of regenerative ability of the mammalian heart is to first consider why, and not only how, this happens. The regenerative ability of the early postnatal heart following resection or ischemic infarction involves regeneration of the lost myocardium and vasculature with restoration of normal myocardial thickness and architecture, and long-term functional recovery. Why would the heart permanently forego such a remarkable regenerative program shortly after birth? The answer may lie in within the fundamental principal of evolutionary tradeoff.